2020
DOI: 10.3390/rs12162663
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Analysis of the Mt. Umyeon Landslide Area Using a Physical Slope Model and Probabilistic Method

Abstract: Every year, many countries carry out landslide susceptibility analyses to establish and manage countermeasures and reduce the damage caused by landslides. Because increases in the areas of landslides lead to new landslides, there is a growing need for landslide prediction to reduce such damage. Among the various methods for landslide susceptibility analysis, statistical methods require information about the landslide occurrence point. Meanwhile, analysis based on physical slope models can estimate stability by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The visualization of the reflectance and the normalization equation/filter values was achieved using interpolation. The ArcGIS software was used for the application of data using a kriging interpolation tool, which works through the correlation between the surrounding values' distance and the values located around a point [46,47]. It should be noted that this can be considered a starting point of the described methodology since it took place in a small region without any satellite image.…”
Section: Applicationmentioning
confidence: 99%
“…The visualization of the reflectance and the normalization equation/filter values was achieved using interpolation. The ArcGIS software was used for the application of data using a kriging interpolation tool, which works through the correlation between the surrounding values' distance and the values located around a point [46,47]. It should be noted that this can be considered a starting point of the described methodology since it took place in a small region without any satellite image.…”
Section: Applicationmentioning
confidence: 99%
“…Numerous researches showed that root cohesion can be drastically reduced following fire lading to slopes more prone to failures (Gehring et al, 2019;Jackson and Roering, 2009;Lanini et al, 2009) The spatial and temporal uncertainty of these input parameters is still one of the major challenges in predicting landslides (Anagnostopoulos et al, 2015;Sidle and Ochiai, 2006;van Westen et al, 2006). To consider this uncertainty, a probabilistic approach can be used (Hammond et al, 1992;Lee et al, 2020;Nilsen, 2000;Strauch et al, 2018). Strauch et al ( 2018) developed a regional model of probabilistic slope failures and applied it to the North Cascades National Park Complex in the state of Washington, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Each study also used different input variables with consideration of classifying the categories of geographical conditions and the obtained values were used for the purpose. In addition, Levenberg–Marquardt and Bayesian regularization algorithms were used as a back propagation method, which has a crucial influence on the outcome of ML 2 , 3 , 19 in finding an optimal weight and bias for prediction 20 . Each method is developed to minimize errors when finding the inflection point through a probability technique.…”
Section: Introductionmentioning
confidence: 99%